The Nature of Punishment Revisited: Reply to Wringe - Hanna, Nathan (Ethical theory and moral practice, 2020)
This paper continues a debate about the following claim: an agent punishes someone only if she aims to harm him. In a series of papers, Bill Wringe argues that this claim is false, I criticize his arguments, and he replies. Here, I argue that his reply fails.